2021
DOI: 10.1042/cs20201372
|View full text |Cite
|
Sign up to set email alerts
|

CRIP1 expression in monocytes related to hypertension

Abstract: Hypertension is a complex and multifactorial disorder caused by lifestyle and environmental factors, inflammation and disease-related genetic factors and is a risk factor for stroke, ischemic heart disease and renal failure. Although circulating monocytes and tissue macrophages contribute to the pathogenesis of hypertension, the underlying mechanisms are poorly understood. Cysteine rich protein 1 (CRIP1) is highly expressed in immune cells, and CRIP1 mRNA expression in monocytes associates with blood pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Indeed, we did find discrete changes in NO-GC and cGKI abundance in CRP4 negative VSMCs and at least partly also in the aorta, respectively, while other components of the pathway were not assessed in detail. In addition, lack of CRP4 might alter the expression of other genes relevant for Ca 2+ handling and may also induce changes in, for instance, highly related LIM proteins [57,104]. Similar compensatory mechanisms involving members of the CRP family have been identified in cardiac muscle [57] and the vasculature [65].…”
Section: Conclusion and Limitations Of The Studymentioning
confidence: 83%
“…Indeed, we did find discrete changes in NO-GC and cGKI abundance in CRP4 negative VSMCs and at least partly also in the aorta, respectively, while other components of the pathway were not assessed in detail. In addition, lack of CRP4 might alter the expression of other genes relevant for Ca 2+ handling and may also induce changes in, for instance, highly related LIM proteins [57,104]. Similar compensatory mechanisms involving members of the CRP family have been identified in cardiac muscle [57] and the vasculature [65].…”
Section: Conclusion and Limitations Of The Studymentioning
confidence: 83%
“…A previous study demonstrated that IGFBP5 , 223 PRDX6 , 224 PKM (pyruvate kinase M1/2) , 225 PRDX1 , 226 and USP22 227 were more highly expressed in diabetic nephropathy. Durgin et al, 228 Zhang et al, 229 Hamada et al, 230 Gong et al, 231 Li et al, 232 Lin et al, 233 and Schweigert et al 234 suggested that CYB5R3, CACNA1A, GLCCI1, CAP1, HSP90AB1, BLVRA (biliverdinreductase A), and CRIP1 were involved in the progression of hypertension. These results suggested that these, cognitive impairment, cardiovascular diseases, obesity, diabetic nephropathy and hypertension responsible genes might influence the development of T2DM through the altered expression.…”
Section: Discussionmentioning
confidence: 99%
“…Cysteine-rich intestinal protein 1 (CRIP1), a LIM protein subfamily, contains a short LIM structural domain (Cai et al, 2017). CRIP1-positive circulating and splenic monocytes have been reported to play an important role in the inflammatory process associated with hypertension, and CRIP1 may influence the interaction of the immune system and the pathogenesis of hypertension (Schweigert et al, 2021). In addition, it can regulate the growth and differentiation of eukaryotic cells (Cai et al, 2017).…”
Section: Discussionmentioning
confidence: 99%